Un acercamiento teórico a la subjetividad juvenil y su relación con la mediación tecnológica. (2021)
The new technologies of the information and the communication ( NTIC) are in the « eye of the hurricane « of the principal anthropological transformation that is emerging nowadays, specially among the young people who were born and raised inside this new way of technological mediation. Young people and other people who have a juvenile condition have converted this new ways of symbolic and material production in their main technologies of subjective transformation, being configured what Donna Haraway called «cyborg subject «. Understanding this phenomenon is an academic challenge for those who investigate the juvenile reality in Colombia and Latinamerica, because, although there is an important technological gap among us and the « first world « countries, in this moment in the top of the iceberg these transformations in the Human Being and in the culture are happening.